Kemampuan Tumbuh Anakan Tumbuhan Nyamplung (Calophyllum inophyllum L.) pada Berbagai Taraf Penggenangan (The Growth Ability of Nyamplung (Calophyllum inophyllum L.) Seedling to Various of Flooding Levels) - Norsamsi NORSAMSI; Siti FATONAH; Dyah IRIANI (Universitas Jambi, 2015)
This study aims to observe the response of nyamplung seedling to various of flooding levels, using a randomized block design with a single factor of five inundation treatments (control, 0 cm or equal the solil surface, 4 cm, 8 cm, 12 cm). Flooding treatment was carried out for 30 days. The observed parameters were growth rate, morphological adaptation, and injury index. Data were analyzed using ANOVA and Duncan Multi Range Taste (DMRT) in the level of 5%.Â The results showed that flooding treatment reduce the growth of nyamplung seedling (fresh weight, height, stem diameter, number of leaves, leaf area, and fesh root weight). Seedling of nyamplung able to survive on equal ground flooding level and 4 cm above the soil surface, classified as moderately tolerant plants. Seedlings were not able to survive in the flooding level of 8 cm and 12 cm, classified as sensitive plants. Morphological adaptations such as lenticels formed by 20% on equal ground surface flooding level and 60%Â on the flooding level of 4 cm.